Chronic Atrial Fibrillation Ablation with Harmonic Scalpel during Mitral Valve Surgery - Alexandre Visconti Brick; Domingo M. Braile (Brazilian Journal of Cardiovascular Surgery)
Abstract Objective To evaluate surgical treatment of chronic atrial fibrillation with ultrasound in patients with mitral valve disease, considering preoperative clinical characteristics of patients undergoing surgical procedure and follow-up in the immediate postoperative period, in hospital and up to 60 months after discharge. Methods: We studied 100 patients with chronic atrial fibrillation and mitral valve disease who underwent surgical treatment using ultrasound ablation. Patient data were reviewed by consulting the control reports, including signs and symptoms, underlying disease, functional class, hospital stay, surgical procedure time, ablation time, immediate complications, and complications at discharged and up to 60 months later. Actuarial curve (Kaplan-Meier) was used for the study of permanence without recurrence after 12, 24, 36, 48 and 60 months. Results: 86% of the patients had rheumatic mitral valve disease, 14% had degeneration of the mitral valve, 40% had mitral regurgitation, and 36% had mitral stenosis. Main symptoms included palpitations related to tachycardia by chronic atrial fibrillation (70%), congestive heart failure (70%), and previous episodes of acute pulmonary edema (27%). Early results showed that 94% of the patients undergoing ultrasound ablation reversed the rate of chronic atrial fibrillation, 86% being in sinus rhythm and 8% in atrioventricular block. At hospital discharge, maintenance of sinus rhythm was observed in 86% of patients and there was recurrence of chronic atrial fibrillation in 8% of patients. At follow-up after 60 months, 83.8% of patients maintained the sinus rhythm. Conclusion: Surgical treatment of chronic atrial fibrillation with ultrasound concomitant with mitral valve surgery is feasible and satisfactory, with maintenance of sinus rhythm in most patients (83.8%) after 60 months of follow-up.